Ocena efektywności zabezpieczenia z użyciem kontraktu swap - Krzeszowski, Wojciech Dawid (Valuation of Effectiveness of the Swap Contract Hedging, 2008)
With a view to earning profit on its operations an enterprise also tries to avert unnecessary risk. One solution is the use of financial hedging instruments. In order to properly record changes in terms of the financial hedging instruments it is essential that the effective and ineffective part of hedging be calculated. The paper focuses on methods of defining the effectiveness of swap contract hedging.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 32, s. 52-57